A positive electrode active material, a manufacturing method, a secondary battery, and an electric device
Patent Information
- Application Number
- CN202510779828.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请所要解决的技术问题是提供一种正极活性材料、制备方法、二次电池和用电设备,以解决相关技术中二次电池存在电池容量降低、循环性能下降以及使用寿命衰减的问题
[0030]本申请实施例所提供的正极活性材料,包括一次颗粒,并且一次颗粒聚集形成二次颗粒;本申请实施例中,将根据二次颗粒的最大截面中孔隙的总数量、二次颗粒的粒径以及二次颗粒的粒径分布参数确定的正极活性材料的收缩因子控制在大于或者等于26个/μm,由此可以通过控制正极活性材料中二次颗粒的最大截面中孔隙的总数量、二次颗粒的粒径以及二次颗粒的粒径分布参数,在增大正极活性材料的比表面积的同时,增大正极活性材料中孔隙的体积,在基于本申请实施例提供的正极活性材料制备的二次电池中,正极活性材料较大的比表面积可以增大正极活性材料与电解质之间的接触面积,提高正极活性材料与电解质之间界面的接触质量,优化二次电池中的离子和电子的传输通道,降低离子和电子的传输阻力,提高离子和电子的传输效率,有利于提高二次电池的电池容量;进一步地,本申请实施例通过增大正极活性材料中孔隙的体积,一方面可以为电解质提供在正极活性材料中的填充空间,进一步提高正极活性材料与电解质之间界面的接触质量,另一方面还可以在二次电池的充电过程中,提高正极活性材料脱锂后的体积收缩程度,为负极活性材料的嵌锂膨胀提供足够膨胀空间,缓解二次电池内部的压力,降低负极活性材料的嵌锂膨胀过程对正极活性材料和负极活性材料造成的挤压和破坏程度,有利于提高二次电池的循环性能并延长二次电池的使用寿命。
Smart Images

Figure CN123017956A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, and in particular to a positive electrode active material, a preparation method, a secondary battery, and an electrical device. Background Technology
[0002] With the increasing demand for renewable energy, secondary batteries are being used more and more widely in electric vehicles, energy storage systems, and various portable electronic devices.
[0003] Solid-state batteries have attracted widespread attention in the industry due to their high energy density and safety. However, the poor interfacial contact between the positive electrode active material and the electrolyte in solid-state batteries hinders ion transport and reduces battery capacity. Furthermore, during charging, the lithium insertion of the negative electrode causes expansion, increasing the internal pressure of the battery. This leads to mutual compression and breakage between the positive and negative electrode active material particles, resulting in decreased cycle performance and reduced lifespan. Summary of the Invention
[0004] The technical problem to be solved by this application is to provide a positive electrode active material, a preparation method, a secondary battery, and an electrical device to solve the problems of reduced battery capacity, decreased cycle performance, and reduced service life of secondary batteries in related technologies.
[0005] To solve the above problems, this application provides the following technical solution:
[0006] This application proposes a positive electrode active material, which comprises primary particles that aggregate to form secondary particles, and the positive electrode active material satisfies the following:
[0007] c = N / (D × Kn90);
[0008] Wherein, c_cells / μm represents the shrinkage factor of the positive electrode active material, which is used to reflect the volume shrinkage characteristics of the positive electrode active material during the delithiation process, and c ≥ 26_cells / μm;
[0009] N represents the total number of pores in the maximum cross-section of the secondary particle;
[0010] Dμm represents the particle size of the secondary particles;
[0011] Kn90 represents the particle size distribution parameter of the secondary particles in the positive electrode active material, which reflects the uniformity of the particle size distribution of the secondary particles in the positive electrode active material.
[0012] Furthermore, in the aforementioned positive electrode active material, the particle size distribution parameters of the secondary particles satisfy:
[0013] Kn90 = (Dn90 - Dn10) / Dn50;
[0014] Wherein, Dn90μm represents the particle size corresponding to a cumulative distribution percentage of 90% for the secondary particles; Dn10μm represents the particle size corresponding to a cumulative distribution percentage of 10% for the secondary particles; and Dn50μm represents the particle size corresponding to a cumulative distribution percentage of 50% for the secondary particles.
[0015] Furthermore, in the positive electrode active material, 0.3 ≤ Kn90 ≤ 1.1.
[0016] Furthermore, in the positive electrode active material, N ≥ 260.
[0017] Furthermore, in the positive electrode active material, 2μm≤D≤9μm.
[0018] Furthermore, the positive electrode active material includes materials with the molecular formula Li. a Ni b Co c Mn d M m N n Compounds of O2;
[0019] Where b+c+d+m+n=1, and 1 <a<1.1,0≤b<1,0<c≤1,0≤d≤0.5,0<m≤0.1,0<n≤0.1;
[0020] M and N are each independently selected from at least one of Ti, Al, Zr, Y, Sr, Nb, W, Sb, Ce, Mg, Co, Mo, V, and B.
[0021] Furthermore, in the positive electrode active material, the particle size Dn50 of the primary particles is 100nm to 300nm; the particle size Dn50 of the primary particles represents the particle size corresponding to the cumulative distribution percentage of the number of primary particles being equal to 50%.
[0022] Furthermore, in the positive electrode active material, the particle size Dn50 of the secondary particles is 3μm to 18μm; the particle size Dn50 of the secondary particles represents the particle size corresponding to the cumulative distribution percentage of the secondary particles being equal to 50%.
[0023] This application also proposes a method for preparing a positive electrode active material, the method comprising:
[0024] A hydroxide precursor material was prepared by mixing a transition metal salt solution, an alkaline solution, and a complexing agent solution.
[0025] The first mixture obtained by mixing the hydroxide precursor material with an alkali metal source and a first additive is subjected to sintering treatment to obtain the raw material.
[0026] Based on the raw materials, the positive electrode active material as described in any one of claims 1 to 8 is prepared.
[0027] This application also proposes a secondary battery, which includes a positive electrode and a negative electrode; the positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, the positive active material layer including the positive active material as described above.
[0028] This application also proposes an electrical device, which includes a secondary battery as described above, and the secondary battery serves as the power supply for the electrical device.
[0029] Compared with related technologies, the embodiments of this application have the following advantages:
[0030] The positive electrode active material provided in this application embodiment includes primary particles, which aggregate to form secondary particles. In this application embodiment, the shrinkage factor of the positive electrode active material, determined based on the total number of pores in the maximum cross-section of the secondary particles, the particle size of the secondary particles, and the particle size distribution parameters of the secondary particles, is controlled to be greater than or equal to 26 pores / μm. Therefore, by controlling the total number of pores in the maximum cross-section of the secondary particles in the positive electrode active material, the particle size of the secondary particles, and the particle size distribution parameters of the secondary particles, the specific surface area of the positive electrode active material can be increased, while simultaneously increasing the volume of pores in the positive electrode active material. In the secondary battery prepared based on the positive electrode active material provided in this application embodiment, the larger specific surface area of the positive electrode active material can increase the contact area between the positive electrode active material and the electrolyte, thereby improving the interface between the positive electrode active material and the electrolyte. Improving contact quality optimizes the transport channels for ions and electrons in the secondary battery, reduces transport resistance, and increases transport efficiency, thus improving battery capacity. Furthermore, by increasing the pore volume in the positive electrode active material, this embodiment provides space for the electrolyte to fill within the material, further improving the contact quality between the positive electrode active material and the electrolyte. Simultaneously, it increases the volume shrinkage of the positive electrode active material after delithiation during charging, providing sufficient expansion space for the lithium insertion expansion of the negative electrode active material. This alleviates internal pressure within the secondary battery and reduces the squeezing and damage caused to both materials by the lithium insertion expansion process, thereby improving cycle performance and extending battery life.
[0031] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Attached Figure Description
[0032] Figure 1 This is a schematic cross-sectional view of a positive electrode active material provided in an embodiment of this application;
[0033] Figure 2 This is a flowchart of the steps in a method for preparing a positive electrode active material provided in an embodiment of this application.
[0034] Explanation of reference numerals in the attached figures:
[0035] 10 - Positive electrode active material; 101 - Secondary particles; 1011 - Primary particles; 1012 - Pores. Detailed Implementation
[0036] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, the application will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] While solid-state batteries offer high energy density and safety, poor interfacial contact between the positive electrode active material and the electrolyte hinders ion transport, reduces battery capacity, and necessitates external pressurization for operation. Furthermore, during charging, the lithium insertion of the negative electrode causes expansion. For silicon-doped negative electrode active materials, this expansion can exceed 30%, increasing with silicon doping. If the external pressure remains constant, the expansion of the negative electrode active material leads to a surge in internal pressure, compressing both the positive and negative electrode active material particles and causing them to break. This results in decreased cycle performance and reduced battery life.
[0038] If the external pressure of a secondary battery is to be controlled to adapt to changes during charging, higher requirements are needed for the external pressure application device, which not only makes industrialization impossible but also increases the manufacturing cost of secondary batteries. Although the ternary cathode active material of lithium nickel cobalt manganese oxide in related technologies shrinks to some extent during charging, the volume shrinkage rate of this type of cathode active material is only about 7%, which is insufficient to alleviate the high stress deformation caused by the expansion of the negative electrode.
[0039] To address the aforementioned problems, this application provides a positive electrode active material, referring to... Figure 1 The positive electrode active material 10 includes primary particles 1011, which aggregate to form secondary particles 101.
[0040] Positive electrode active material 10 satisfies:
[0041] c=N / (D×Kn90) (1)
[0042] Wherein, c represents the shrinkage factor of the positive electrode active material 10, with the unit being: cells / μm. The shrinkage factor is used to reflect the volume shrinkage characteristics of the positive electrode active material 10 during the delithiation process, and c≥26 cells / μm; wherein, the delithiation process of the positive electrode active material 10 specifically refers to the charging process of the secondary battery prepared based on the positive electrode active material 10. In this embodiment, the specific surface area of the positive electrode active material 10 and the volume of the pores 1012 in the positive electrode active material 10 can be adjusted by regulating the size of the shrinkage factor. This allows the battery capacity of the secondary battery prepared based on the positive electrode active material 10 and the degree of volume shrinkage of the positive electrode active material 10 during the charging process to achieve a good balance, thereby meeting the requirements for battery capacity, cycle performance, and service life of the secondary battery in practical application scenarios. Specifically, when c ≥ 26 pores / μm, the battery capacity of the secondary battery can be increased while alleviating the internal pressure of the secondary battery during the charging process, thereby improving the cycle performance and extending the service life of the secondary battery. Specifically, the total number N of pores 1012 in the maximum cross-section of the secondary particles 101, the particle size D of the secondary particles 101, and the particle size distribution parameter Kn90 of the secondary particles 101 can be adjusted to ensure that the positive electrode active material 10 satisfies c ≥ 26 pores / μm.
[0043] It should be noted that the specific surface area of the positive electrode active material 10 refers to the total surface area of a unit mass of the positive electrode active material 10, which includes the surface of the primary particles 1011 and the surface of the secondary particles 101 in a unit mass of the positive electrode active material 10.
[0044] It is understood that the secondary battery prepared based on the positive electrode active material 10 provided in the embodiments of this application includes a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material 10 provided in the embodiments of this application.
[0045] The volume of the pores 1012 in the positive electrode active material 10 includes: the volume of the pores 1012 formed between the secondary particles 101 in the positive electrode active material layer, and the volume of the pores 1012 formed between the primary particles 1011 in the secondary particles 101.
[0046] N represents the total number of pores 1012 in the maximum cross-section of the secondary particle 101, expressed in units of pores; wherein, the maximum cross-section of the secondary particle 101 is the cross-section along the particle diameter direction of the secondary particle 101. In some embodiments, to improve the accuracy of the total number of pores 1012 in the maximum cross-section of the secondary particle 101, the average of the total number of pores 1012 in the maximum cross-section of at least 5 different secondary particles 101 can be used as the total number N used in Formula 1 to calculate the shrinkage factor c.
[0047] D represents the particle size of the secondary particle 101, in μm; specifically, the particle size of the secondary particle 101 refers to the maximum straight-line distance between any two points on the surface of the secondary particle 101; in this embodiment, the shape of the secondary particle 101 can be spherical or near-spherical, and the shape of the maximum cross-section of the secondary particle 101 can be as follows. Figure 1 The circle or near-circle shown.
[0048] Kn90 represents the particle size distribution parameter of the secondary particles 101 in the positive electrode active material 10. This particle size distribution parameter reflects the uniformity of the particle size distribution of the secondary particles 101 in the positive electrode active material 10. Specifically, the smaller the Kn90, the more uniform the particle size of the secondary particles 101 in the positive electrode active material 10; the larger the Kn90, the greater the difference in particle size among the secondary particles 101 in the positive electrode active material 10.
[0049] Reference Figure 1The more uniform the particle size distribution of the secondary particles 101 in the positive electrode active material 10, the more consistent the particle size of the secondary particles 101 becomes. In the positive electrode active material layer, the volume of the pores 1012 formed between the secondary particles 101 in the positive electrode active material 10 also increases. As the volume of the pores 1012 formed between the secondary particles 101 increases, the volume shrinkage of the positive electrode active material 10 during the delithiation process can be improved, which is beneficial to alleviate the internal pressure of the secondary battery during charging, reduce the degree of compression and damage to the positive and negative electrode active material particles caused by the lithium insertion expansion process of the negative electrode active material, improve the cycle performance of the secondary battery and extend its service life. However, as the volume of the pores 1012 formed between the secondary particles 101 increases, the spacing between the secondary particles 101 in the positive electrode active material 10 will increase, making it difficult for the electrolyte to form a continuous conductive network, resulting in a decrease in the battery capacity of the secondary battery. Correspondingly, the greater the difference in particle size between the secondary particles 101 in the positive electrode active material 10, the smaller secondary particles 101 in the positive electrode active material 10 can fill the pores 1012 formed between the larger secondary particles 101, thereby reducing the volume of the pores 1012 formed between the secondary particles 101 in the positive electrode active material 10. As the volume of the pores 1012 formed between the secondary particles 101 decreases, the spacing between the secondary particles 101 in the positive electrode active material 10 can be reduced, improving the continuity of the conductive network formed by the electrolyte, and thus increasing the battery capacity based on the secondary battery. However, as the volume of the pores 1012 formed between the secondary particles 101 decreases, the volume shrinkage of the positive electrode active material 10 during the delithiation process decreases, resulting in an increase in the internal pressure of the secondary battery during the charging process.
[0050] The particle size of the secondary particles 101 in the positive electrode active material 10 determines the size of the specific surface area of the secondary particles 101. Specifically, the smaller the particle size of the secondary particles 101, the larger the specific surface area of the secondary particles 101, and the larger the specific surface area of the positive electrode active material 10. This can increase the contact area between the positive electrode active material 10 and the electrolyte, optimize the ion and electron transport channels in the secondary battery, improve the ion and electron transport efficiency in the secondary battery, and increase the battery capacity. However, the smaller the particle size of the secondary particles 101, the smaller the volume of the pores 1012 formed between the secondary particles 101, which leads to a decrease in the volume shrinkage of the positive electrode active material 10 during the delithiation process and an increase in the internal pressure of the secondary battery during the charging process. Correspondingly, the larger the particle size of the secondary particles 101, the larger the volume of the pores 1012 formed between the secondary particles 101, which can improve the volume shrinkage of the positive electrode active material 10 during the delithiation process. However, as the particle size of the secondary particles 101 increases, the specific surface area of the secondary particles 101 decreases, resulting in a decrease in the specific surface area of the positive electrode active material 10 and a smaller contact area between the positive electrode active material 10 and the electrolyte. This leads to an increase in the resistance to ion and electron transport in the secondary battery, reducing the ion and electron transport efficiency and the battery capacity of the secondary battery.
[0051] The greater the total number of pores 1012 in the maximum cross-section of the secondary particles 101, the greater the number of pores 1012 formed between the primary particles 1011 in the secondary particles 101. The greater the volume shrinkage of the positive electrode active material 10 during the delithiation process, the better it is to alleviate the internal pressure of the secondary battery during charging, reduce the degree of compression and damage to the positive and negative electrode active material particles caused by the lithium insertion expansion process of the negative electrode active material, improve the cycle performance of the secondary battery and extend its service life. Moreover, the greater the number of pores 1012 in the maximum cross-section of the secondary particles 101, the more electrolyte can enter the interior of the secondary particles 101 and contact the primary particles 1011 to form a good interface contact, which is conducive to further reducing the transport resistance of ions and electrons in the secondary battery, improving the transport efficiency of ions and electrons in the secondary battery, and thus increasing the battery capacity of the secondary battery.
[0052] It should be noted that the positive electrode active material 10 provided in the embodiments of this application can be applied to at least one of all-solid-state secondary batteries, semi-solid-state secondary batteries, and liquid secondary batteries.
[0053] It is understood that when the positive electrode active material 10 provided in the embodiments of this application is applied to an all-solid-state secondary battery, the interface between the positive electrode active material 10 and the electrolyte is a solid-solid interface; when the positive electrode active material 10 provided in the embodiments of this application is applied to a liquid secondary battery, the interface between the positive electrode active material 10 and the electrolyte is a solid-liquid interface.
[0054] In this embodiment, by adjusting the total number of pores 1012 in the maximum cross-section of the secondary particles 101, the diameter of the secondary particles 101, and the particle size distribution parameters of the secondary particles 101, the shrinkage factor of the positive electrode active material 10 is made greater than or equal to 26 pores / μm. This allows the specific surface area of the positive electrode active material 10 and the volume of the pores 1012 in the positive electrode active material 10 to reach a relatively balanced state. While increasing the specific surface area of the positive electrode active material 10, the volume of the pores 1012 in the positive electrode active material 10 is also increased. In the secondary battery prepared based on the positive electrode active material 10 provided in this embodiment, the larger specific surface area of the positive electrode active material 10 can increase the contact area between the positive electrode active material 10 and the electrolyte, improve the contact quality of the interface between the positive electrode active material 10 and the electrolyte, and optimize the secondary battery. Improving the transport channels for ions and electrons, reducing the transport resistance of ions and electrons, and improving the transport efficiency of ions and electrons are beneficial to increasing the battery capacity of secondary batteries. In this embodiment, by increasing the volume of the pores 1012 in the positive electrode active material 10, on the one hand, it can provide filling space for the electrolyte in the positive electrode active material 10, further improving the contact quality of the interface between the positive electrode active material 10 and the electrolyte. On the other hand, it can also improve the volume shrinkage of the positive electrode active material 10 after delithiation during the charging process of the secondary battery, providing sufficient expansion space for the lithium intercalation expansion of the negative electrode active material, relieving the internal pressure of the secondary battery, reducing the degree of compression and damage to the positive and negative electrode active material particles caused by the lithium intercalation expansion process of the negative electrode active material, improving the cycle performance of the secondary battery and extending its service life.
[0055] Optionally, in the positive electrode active material 10 provided in the embodiments of this application, the particle size distribution parameters of the secondary particles 101 satisfy:
[0056] Kn90=(Dn90-Dn10) / Dn50 (2)
[0057] Wherein, Dn90μm represents the particle size corresponding to a cumulative distribution percentage of secondary particles 101 equal to 90%; Dn10μm represents the particle size corresponding to a cumulative distribution percentage of secondary particles 101 equal to 10%; and Dn50μm represents the particle size corresponding to a cumulative distribution percentage of secondary particles 101 equal to 50%. It can be understood that the more uniform the particle size of the secondary particles 101 in the positive electrode active material 10, the smaller the difference between Dn90 and Dn10, and the smaller the Kn90 calculated by formula 2. Conversely, the greater the difference in particle size among the secondary particles 101 in the positive electrode active material 10, the greater the difference between Dn90 and Dn10, and the larger the Kn90 calculated by formula 2.
[0058] In this embodiment of the application, the particle size distribution parameter Kn90 of the secondary particles 101 is controlled by adjusting the particle size Dn90, particle size Dn10 and particle size Dn50. This improves the accuracy and operability of controlling the particle size distribution parameter Kn90 of the secondary particles 101.
[0059] Optionally, in the positive electrode active material 10 provided in this application embodiment, 0.3≤Kn90≤1.1; in this application embodiment, the particle size distribution parameter Kn90 of the secondary particles 101 is controlled within the range of 0.3 to 1.1, which can adjust the uniformity of the particle size distribution of the secondary particles 101 in the positive electrode active material 10 to such that the volume shrinkage of the positive electrode active material 10 during the delithiation process is sufficient to alleviate the internal pressure during the charging process of the secondary battery, improve the cycle performance of the secondary battery and extend the service life of the secondary battery, and at the same time minimize the spacing between the secondary particles 101 in the positive electrode active material 10, improve the continuity of the conductive network formed by the electrolyte, and thus improve the battery capacity of the secondary battery, so that the battery capacity, cycle performance and service life of the secondary battery prepared based on this application embodiment achieve a good balance.
[0060] Optionally, in the positive electrode active material 10 provided in this application embodiment, N ≥ 260. In this application embodiment, the total number N of pores 1012 in the maximum cross-section of the secondary particles 101 is controlled to be greater than or equal to 260. This can increase the number of pores 1012 formed between the primary particles 1011 in the secondary particles 101, thereby increasing the volume shrinkage of the positive electrode active material 10 during the delithiation process, further alleviating the internal pressure of the secondary battery during charging, reducing the degree of compression and damage caused to the positive and negative electrode active material particles by the lithium insertion expansion process of the negative electrode active material, improving the cycle performance of the secondary battery and extending its service life. Moreover, the increased number of pores 1012 formed between the primary particles 1011 in the secondary particles 101 can also promote the electrolyte to enter the interior of the secondary particles 101 and contact with the primary particles 1011 to form a good interface contact, which is beneficial to further reduce the transport resistance of ions and electrons in the secondary battery, improve the transport efficiency of ions and electrons in the secondary battery, and increase the battery capacity of the secondary battery.
[0061] Optionally, in the positive electrode active material 10 provided in the embodiments of the present application, 2μm≤D≤9μm; in the embodiments of the present application, the particle size D of the secondary particles 101 is controlled within the range of 2μm to 9μm. In this way, the particle size of the secondary particles 101 can be adjusted to not only increase the volume of the pores 1012 formed between the secondary particles 101, so that the volume shrinkage degree of the positive electrode active material 10 during the delithiation process is sufficient to alleviate the internal pressure during the charging process of the secondary battery, improve the cycle performance of the secondary battery and prolong the service life of the secondary battery, but also increase the specific surface area of the positive electrode active material 10, optimize the transmission channels for ions and electrons in the secondary battery, improve the transmission efficiency of ions and electrons in the secondary battery and the battery capacity of the secondary battery, so that the battery capacity, cycle performance and service life of the secondary battery prepared based on the embodiments of the present application reach a good balanced state.
[0062] Optionally, the positive electrode active material 10 provided in the embodiments of the present application includes a compound with the molecular formula Li a Ni b Co c Mn d M m N n O2; wherein b+c+d+m+n=1, and 1<a<1.1, 0≤b<1, 0<c≤1, 0≤d≤0.5, 0<m≤0.1, 0<n≤0.1; M and N are each independently selected from at least one of Ti, Al, Zr, Y, Sr, Nb, W, Sb, Ce, Mg, Co, Mo, V, B.
[0063] Wherein, M as a doping element is doped into the positive electrode active material 10, which can promote the orientation of the primary particles 1011 in the positive electrode active material 10, reduce the stress concentration at the grain boundary of the positive electrode active material 10 during the charge-discharge cycle of the secondary battery, and is beneficial to improving the stability of the crystal structure of the positive electrode active material 10 and the cycle performance of the secondary battery.
[0064] N can form a coating layer of the secondary particles 101, which is beneficial to reducing the side reaction between the secondary particles 101 in the positive electrode active material 10 and the electrolyte, reducing the dissolution amount of metal ions in the positive electrode active material 10 at the interface between the positive electrode active material 10 and the electrolyte, and is beneficial to improving the battery capacity, cycle performance and service life of the secondary battery.
[0065] Optionally, in the positive electrode active material 10 provided in the embodiments of this application, the particle size Dn50 of the primary particles 1011 is 100nm to 300nm. Within this range, sufficient pores 1012 can be formed inside the secondary particles 101 to alleviate the internal pressure of the secondary battery during charging, improve the cycle performance of the secondary battery and extend its service life, and ensure that the positive electrode active material 10 has sufficient specific surface area to contact the electrolyte, optimize the transport channels of ions and electrons in the secondary battery, and improve the battery capacity of the secondary battery.
[0066] In some embodiments, the particle size Dn50 of the primary particle 1011 can be a range of one or any two of 100nm, 150nm, 200nm, 250nm and 300nm.
[0067] Wherein, the particle size Dn50 of primary particles 1011 represents the particle size corresponding to the cumulative distribution percentage of primary particles 1011 equal to 50%.
[0068] Optionally, in the positive electrode active material 10 provided in this application embodiment, the particle size Dn50 of the secondary particles 101 is 3μm to 18μm. Within this range, the volume of the pores 1012 formed between the secondary particles 101 can be increased, so that the volume shrinkage of the positive electrode active material 10 during the delithiation process is sufficient to alleviate the internal pressure during the charging process of the secondary battery, improve the cycle performance of the secondary battery and extend the service life of the secondary battery. At the same time, it ensures that the positive electrode active material 10 has sufficient specific surface area to contact the electrolyte, optimizes the ion and electron transport channels in the secondary battery, improves the ion and electron transport efficiency in the secondary battery and the battery capacity of the secondary battery, so that the battery capacity, cycle performance and service life of the secondary battery prepared based on the embodiment of this application reach a good balance.
[0069] In some embodiments, the particle size Dn50 of the secondary particles 101 can be a range of one or any two of 3μm, 5μm, 9μm, 12μm, 15μm and 18μm.
[0070] Wherein, the particle size Dn50 of secondary particles 101 represents the particle size corresponding to the cumulative distribution percentage of secondary particles 101 being equal to 50%.
[0071] Reference Figure 2 This application also provides a method for preparing a positive electrode active material, the method comprising steps S101 to S103:
[0072] Step S101: Mix the transition metal salt solution, the alkaline solution and the complexing agent solution to prepare the hydroxide precursor material.
[0073] Step S102: The first mixture obtained by mixing the hydroxide precursor material with the alkali metal source and the first additive is subjected to sintering treatment to obtain the raw material.
[0074] Step S103: Based on the raw materials, a positive electrode active material is prepared.
[0075] The method for preparing the positive electrode active material provided in this application can be used to prepare the positive electrode active material as described in any of the preceding claims.
[0076] The transition metals in the positive electrode active material include Ni, Co, and Mn, and the transition metal salts may include sulfates of Ni, Co, and Mn. In step S101:
[0077] First, according to the molar ratio of Ni, Co, and Mn in the positive electrode active material, the sulfates of Ni, Co, and Mn are mixed and dissolved to obtain a transition metal salt solution; the concentration of the transition metal salt solution is 1 mol / L to 10 mol / L. Sodium hydroxide or sodium carbonate is dissolved to obtain an alkaline solution; the concentration of the alkaline solution is 1 mol / L to 10 mol / L. Ammonia water is diluted to a concentration of 1 g / L to 9 g / L to obtain a complexing agent solution.
[0078] Then, the transition metal salt solution, alkaline solution, and complexing agent solution are added to the reactor in parallel flow. An inert gas is introduced into the reactor for atmosphere protection. By controlling the flow rates of the alkaline solution and complexing agent solution into the reactor, the pH of the mixed solution formed by the transition metal salt solution, alkaline solution, and complexing agent solution in the reactor is controlled to be 10.5–12.9, the reaction temperature in the reactor is 40℃–70℃, the stirring speed is 100rpm–500rpm, and the reaction time is 10h–90h, to obtain a hydroxide precursor slurry. The flow rate of the transition metal salt solution into the reactor is 5.0%–11% of the reactor volume per hour.
[0079] Finally, the hydroxide precursor slurry was subjected to solid-liquid separation, washing, drying, and sieving to obtain the hydroxide precursor material Ni. b Co c Mn d (OH)₂; In some embodiments, the hydroxide precursor material is spherical. The hydroxide precursor material includes materials with the molecular formula Ni. b Co c Mn d Compounds of (OH)₂, where 0 ≤ b < 1, 0 <c≤1,0≤d≤0.5。
[0080] In step S102, firstly, the hydroxide precursor material prepared in step S101 is mixed with an alkaline metal source and a first additive to obtain a first mixture; then, the first mixture is sintered to obtain the raw material.
[0081] Among them, the alkaline metal source may include, but is not limited to, lithium source, sodium source and potassium source; the lithium source may include, but is not limited to, lithium carbonate, lithium hydroxide, lithium nitrate and so on.
[0082] The molar ratio of the hydroxide precursor material to the alkali metal source is 1:1.01 to 1.05; the molar ratio of the hydroxide precursor material to the first additive is 1:0.0001 to 0.03.
[0083] The first additive includes at least one of the following: oxide of element M, hydroxide of element M, oxalate of element M, and nitrate of element M; M is selected from at least one of Al, Zr, Y, Ti, Sb, W, Ce, Mg, Mo, and V.
[0084] In step S102, the first mixture is sintered at a temperature of 700℃ to 950℃ for a duration of 6 hours to 15 hours, and the sintering atmosphere includes at least one of air and oxygen. It should be noted that the first additive decomposes during the sintering process, generating gas and forming pores between the primary particles. In this embodiment, the number of pores formed between the primary particles in the secondary particles can be controlled by adjusting the sintering temperature and duration. Specifically, the higher the sintering temperature and the longer the sintering time, the fewer pores are formed between the primary particles in the secondary particles; conversely, the lower the sintering temperature and the shorter the sintering time, the more pores are formed between the primary particles in the secondary particles.
[0085] Furthermore, in step S102, the proportion of oxygen in the sintering atmosphere can be determined based on the Ni content in the positive electrode active material. Specifically, when the Ni content in the positive electrode active material is less than 60 mol%, the sintering atmosphere can be air. As the Ni content in the positive electrode active material increases, more oxygen is required in the sintering atmosphere. When the Ni content is greater than 80 mol%, the sintering atmosphere can be oxygen. When the Ni content in the positive electrode active material is greater than or equal to 60 mol% and less than or equal to 80 mol%, the sintering atmosphere includes both air and oxygen, and the ratio between air and oxygen can be adjusted based on the specific Ni content in the positive electrode active material.
[0086] In some embodiments, in step S103, the raw material obtained in step S102 is washed with water, and the washed raw material is identified as the positive electrode active material.
[0087] The process of washing the raw material obtained in step S102 is as follows: the raw material is mixed with pure water at a mass ratio of 2:1, stirred at 300 rpm for 3 minutes, filtered, and the filter cake obtained by filtration is dried in a vacuum oven at 150℃ for 6 hours to obtain the washed raw material.
[0088] In other embodiments, in step S103, firstly, the raw material obtained in step S102 is washed with water to obtain washed raw material; then, the washed raw material is mixed with a second additive to obtain a second mixture; finally, the second mixture is sintered and the sintered product is crushed to obtain a positive electrode active material.
[0089] The second additive includes an oxide of nitrogen; N is selected from at least one of Ti, Al, Zr, Y, Sr, Nb, W, Sb, Ce, Mg, Co, Mo, V, and B.
[0090] The molar ratio of the washed raw material to the second additive is 1:0.001 to 0.01.
[0091] In step S103, the second mixture is sintered at a temperature of 200°C to 600°C for a duration of 6 hours to 12 hours, and the sintering atmosphere includes at least one of air and oxygen.
[0092] It should be noted that the second additive melts and grows on the surface of the secondary particles under the high-temperature conditions of sintering.
[0093] The coating layer is formed to protect the secondary particles, which helps to reduce the side reactions between the secondary particles and the electrolyte in the positive electrode active material, and reduces the amount of metal ions dissolved in the positive electrode active material at the interface between the positive electrode active material and the electrolyte. This helps to improve the battery capacity, cycle performance and service life of the secondary battery.
[0094] The method for preparing the positive electrode active material provided in this application embodiment, by adjusting the process parameters of each step, allows the prepared positive electrode active material to include primary particles, which aggregate to form secondary particles. Furthermore, by adjusting the total number of pores in the maximum cross-section of the secondary particles, the diameter of the secondary particles, and the particle size distribution parameters of the secondary particles, the shrinkage factor of the positive electrode active material can be made greater than or equal to 26 pores / μm. This allows for a more balanced state between the specific surface area and the pore volume of the positive electrode active material, increasing both the specific surface area and the pore volume. In the secondary battery prepared based on the positive electrode active material provided in this application embodiment, the larger specific surface area of the positive electrode active material can increase the contact area between the positive electrode active material and the electrolyte, improving the contact between the positive electrode active material and the electrolyte. Improving the contact quality at the interface between the positive electrode and the electrolyte optimizes the transport channels for ions and electrons in the secondary battery, reduces the transport resistance of ions and electrons, and improves the transport efficiency of ions and electrons, which is beneficial to increasing the battery capacity of the secondary battery. In this embodiment, by increasing the volume of pores in the positive electrode active material, on the one hand, it can provide filling space for the electrolyte in the positive electrode active material, further improving the contact quality at the interface between the positive electrode active material and the electrolyte. On the other hand, it can also increase the volume shrinkage of the positive electrode active material after delithiation during the charging process of the secondary battery, providing sufficient expansion space for the lithium insertion expansion of the negative electrode active material, relieving the internal pressure of the secondary battery, reducing the degree of compression and damage to the positive and negative electrode active material particles caused by the lithium insertion expansion process of the negative electrode active material, improving the cycle performance of the secondary battery and extending its service life.
[0095] This application embodiment also provides a secondary battery, the secondary battery including a positive electrode and a negative electrode; the positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, the positive active material layer including the positive active material as described above.
[0096] The above-described secondary battery embodiments include the aforementioned positive electrode active material and achieve the same technical effect. To avoid repetition, they will not be described again here. For relevant details, please refer to the description of the positive electrode active material embodiments.
[0097] The aforementioned positive electrode active material layer further includes a conductive agent and a binder; the conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, hard carbon, carbon fiber, and carbon microspheres; the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.
[0098] In the case of a liquid battery, the negative electrode includes a negative current collector and a negative active material layer disposed on the negative current collector. The negative active material layer can be a negative active material used in secondary batteries. The negative active material can be selected from metallic negative active materials or non-metallic negative active materials. The metallic negative active material can be selected from metal foils or alloy compounds such as sodium, sodium alloys, tin, and antimony. The non-metallic negative active material can be selected from any one or a combination of at least two of hard carbon, soft carbon, graphite, and silicon suboxide.
[0099] The negative electrode sheet also includes conductive agents and binders; the conductive agents include one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene; the binders include sodium carboxymethyl cellulose (CMC) based binders and resin-based binders.
[0100] Optionally, the carboxymethyl cellulose-based adhesive includes one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose; and / or the resin-based adhesive includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), and polyacrylonitrile (PAN).
[0101] When the secondary battery is an all-solid-state battery, the negative electrode can be any of the following: graphite-based negative electrode, silicon-based negative electrode, or metal negative electrode.
[0102] The secondary battery provided in this application also includes an electrolyte.
[0103] The electrolyte acts as a conductor of ions between the positive and negative electrodes. The electrolyte can be liquid, gel-like, or entirely solid. In some embodiments, the electrolyte is a liquid electrolyte solution comprising an electrolyte salt and a solvent. The electrolyte salt is a lithium salt, and the solvent includes cyclic ester solvents and chain ester solvents. In some embodiments, the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate, butenyl carbonate, fluoroethylene carbonate, and γ-butyrolactone; the chain ester solvent includes at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, and diphenyl carbonate. In some embodiments, the organic solvent includes ethylene carbonate, propylene carbonate, and methyl ethyl carbonate.
[0104] In some embodiments, the electrolyte is a solid electrolyte, which may be a sulfide solid electrolyte; the sulfide solid electrolyte includes at least one of the following: Li10GeP2S12 type, Thio-LISICON type, Li2S-P2S5 type, and silver-germanium sulfide type.
[0105] In the case of a liquid battery provided in this application, the secondary battery also includes a separator.
[0106] In practical applications, when the secondary battery is a liquid battery, the negative electrode, separator and positive electrode can be stacked in sequence and wound to obtain a core. The core is then packaged to obtain a bare cell. After baking, the bare cell is injected with liquid, formed, repackaged and sorted to obtain a liquid secondary battery.
[0107] When the secondary battery is an all-solid-state battery, the positive electrode, solid electrolyte, and negative electrode can be stacked in sequence in a solid-state battery mold and then cured to obtain an all-solid-state secondary battery.
[0108] This application also proposes an electrical device, wherein the electrical device includes a secondary battery as described above, and the secondary battery serves as the power supply for the electrical device.
[0109] The above-described electrical equipment embodiment includes the aforementioned secondary battery and achieves the same technical effect. To avoid repetition, it will not be described again here. For relevant details, please refer to the description of the secondary battery embodiment.
[0110] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0111] The present application will be described in detail below through embodiments.
[0112] Example 1
[0113] (1) Preparation of hydroxide precursor materials:
[0114] First, nickel sulfate, cobalt sulfate, and manganese sulfate were dissolved in pure water at a molar ratio of 92:5:3 to obtain a transition metal salt solution with a concentration of 2 mol / L; sodium hydroxide was dissolved in pure water to prepare an alkaline solution with a concentration of 7 mol / L; and ammonia was diluted to a solution with a concentration of 5 g / L to obtain a complexing agent solution.
[0115] Then, the transition metal salt solution, alkaline solution, and complexing agent solution were added to the reactor in a co-current flow. Argon gas was introduced into the reactor for atmosphere protection. By controlling the flow rates of the alkaline solution and complexing agent solution into the reactor, the pH of the mixed solution formed by the transition metal salt solution, alkaline solution, and complexing agent solution in the reactor was controlled to be 12.1. The reaction temperature in the reactor was 40℃, the stirring speed was 300 rpm, and the reaction time was 36 h. When the particle size of the solid particles in the mixed solution reached 3.9 μm, the hydroxide precursor slurry was obtained. The flow rate of the transition metal salt solution into the reactor was 8% of the reactor volume / h.
[0116] Finally, the hydroxide precursor slurry was subjected to solid-liquid separation, washing, drying, and sieving to obtain the hydroxide precursor material Ni. 0.92 Co 0.05 M 0.03 (OH)2.
[0117] (2) Preparation of raw materials:
[0118] First, the hydroxide precursor material prepared in step (1) is mixed with lithium hydroxide at a molar ratio of 1:1.03, and then 1% mol of aluminum oxalate as the first additive is added to obtain the first mixture. Then, the mixture is sintered for 12 hours at 730°C under a pure oxygen atmosphere. After cooling, crushing, and sieving, polycrystalline raw material Li is obtained. 1.03 Ni 0.92 Co 0.05 Mn 0.02 Al 0.01 O2.
[0119] (3) Preparation of positive electrode active material:
[0120] First, the raw material prepared in step (2) is mixed with pure water at a mass ratio of 2:1, stirred at 300 rpm for 3 min and then filtered. The filter cake obtained by filtration is dried in a vacuum oven at 150 ℃ for 6 h to obtain the raw material after water washing.
[0121] Then, the washed raw material was mixed with 0.1% mol boric acid and 0.1% mol niobium pentoxide, and sintered at 300℃ for 6 hours in a pure oxygen atmosphere. After cooling and crushing, polycrystalline positive electrode active material Li was obtained. 1.03 Ni 0.92 Co 0.05 Mn 0.018 Al 0.01 B 0.001 Nb 0.001 O2; wherein, the B element in boric acid and the Nb element in niobium pentoxide are measured in molar ratio.
[0122] (4) Preparation of positive electrode sheet
[0123] The positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride prepared in step (3) are added to a container in a mass ratio of 79:18.5:1:1.5. After stirring evenly, a positive electrode slurry is obtained. The positive electrode slurry is coated on aluminum foil and dried to obtain a positive electrode sheet.
[0124] (5) Preparation of secondary batteries:
[0125] In a glove box filled with argon (H2O<1ppm, O2<1ppm), the positive electrode sheet prepared in step (4), the Li2S-P2S5 type solid electrolyte, and the metal indium negative electrode sheet are stacked in sequence in a solid battery mold and then cured. The curing temperature is adjusted to 60℃ and the curing time is 24h to obtain an all-solid-state secondary battery.
[0126] Example 2
[0127] The difference between Example 2 and Example 1 is as follows:
[0128] In step (1), ammonia water is diluted to a concentration of 7 g / L to obtain a complexing agent solution; by controlling the flow rate of the alkaline solution and the complexing agent solution into the reactor, the pH of the mixed solution formed by the transition metal salt solution, alkaline solution and complexing agent solution in the reactor is controlled to be 11.5, the reaction temperature in the reactor is 40℃, the stirring speed is 300 rpm, the reaction time is 45 h, and the particle size of the solid particles in the mixture reaches 5.4 μm to obtain the hydroxide precursor slurry;
[0129] In step (2), the hydroxide precursor material prepared in step (1) is mixed with lithium hydroxide at a molar ratio of 1:1.03, and then 1%mol of zirconium oxalate, the first additive, is added to obtain the first mixture.
[0130] In step (3), the polycrystalline positive electrode active material obtained after cooling and crushing is Li. 1.03 Ni 0.92 Co0.05 Mn 0.018 Zr 0.01 B 0.001 Nb 0.001 O2.
[0131] Example 3
[0132] The difference between Example 3 and Example 1 is as follows:
[0133] In step (1), ammonia water is diluted to a concentration of 4 g / L to obtain a complexing agent solution; by controlling the flow rate of the alkaline solution and the complexing agent solution into the reactor, the pH of the mixed solution formed by the transition metal salt solution, alkaline solution and complexing agent solution in the reactor is controlled to be 12.5, the reaction temperature in the reactor is 50℃, the stirring speed is 350 rpm, the reaction time is 25 h, and the particle size of the solid particles in the mixture reaches 2.1 μm, the hydroxide precursor slurry is obtained;
[0134] In step (2), the hydroxide precursor material prepared in step (1) is mixed with lithium hydroxide at a molar ratio of 1:1.03, and then 1.5% mol of zirconium oxalate is added to obtain the first mixture;
[0135] In step (3), the polycrystalline positive electrode active material obtained after cooling and crushing is Li. 1.03 Ni 0.92 Co 0.05 Mn 0.018 Zr 0.015 B 0.001 Nb 0.001 O2.
[0136] Example 4
[0137] The difference between Example 4 and Example 1 is as follows:
[0138] In step (1), ammonia water is diluted to a concentration of 5 g / L to obtain a complexing agent solution. By controlling the flow rate of the alkaline solution and the complexing agent solution into the reactor, the pH of the mixed solution formed by the transition metal salt solution, alkaline solution and complexing agent solution in the reactor is controlled to be 10.9, the reaction temperature in the reactor is 45℃, the stirring speed is 280 rpm, the reaction time is 80 h, and the particle size of the solid particles in the mixture reaches 8.9 μm to obtain the hydroxide precursor slurry.
[0139] Example 5
[0140] The difference between Example 5 and Example 1 is:
[0141] In step (1), ammonia water is diluted to a concentration of 5 g / L to obtain a complexing agent solution. By controlling the flow rate of the alkaline solution and the complexing agent solution into the reactor, the pH of the mixed solution formed by the transition metal salt solution, alkaline solution and complexing agent solution in the reactor is controlled to be 11.2. The reaction temperature in the reactor is 45℃, the stirring speed is 450 rpm, and the reaction time is 65 h. When the particle size of the solid particles in the mixture reaches 7.8 μm, the hydroxide precursor slurry is obtained.
[0142] Comparative Example 1
[0143] The difference between Comparative Example 1 and Example 1 is as follows:
[0144] In step (1), ammonia water is diluted to a concentration of 4 g / L to obtain a complexing agent solution; by controlling the flow rate of the alkaline solution and the complexing agent solution into the reactor, the pH of the mixed solution formed by the transition metal salt solution, alkaline solution and complexing agent solution in the reactor is controlled to be 10.2, the reaction temperature in the reactor is 45℃, the stirring speed is 400 rpm, the reaction time is 95 h, and the particle size of the solid particles in the mixture reaches 10.5 μm to obtain the hydroxide precursor slurry;
[0145] In step (2), the hydroxide precursor material prepared in step (1) is mixed with lithium hydroxide at a molar ratio of 1:1.03, and then 1% mol of aluminum oxide is added to obtain the first mixture;
[0146] In step (3), the polycrystalline positive electrode active material obtained after cooling and crushing is Li. 1.03 Ni 0.92 Co 0.05 Mn 0.018 Al 0.01 B 0.001 Nb 0.001 O2.
[0147] Comparative Example 2
[0148] The difference between Comparative Example 2 and Example 1 is as follows:
[0149] In step (1), ammonia water is diluted to a concentration of 5.5 g / L to obtain a complexing agent solution; by controlling the flow rate of the alkaline solution and the complexing agent solution into the reactor, the pH of the mixed solution formed by the transition metal salt solution, alkaline solution and complexing agent solution in the reactor is controlled to be 10.6, the reaction temperature in the reactor is 45℃, the stirring speed is 650 rpm, the reaction time is 120 h, and after the particle size of the solid particles in the mixture reaches 13.4 μm, the hydroxide precursor slurry is obtained;
[0150] In step (2), the hydroxide precursor material prepared in step (1) is mixed with lithium hydroxide at a molar ratio of 1:1.03, and then 1% mol of aluminum hydroxide is added to obtain the first mixture;
[0151] In step (3), the polycrystalline positive electrode active material obtained after cooling and crushing is Li. 1.03 Ni 0.92 Co 0.05 Mn 0.018 Al 0.01 B 0.001 Nb 0.001 O2.
[0152] The process parameters for preparing the positive electrode active materials in each embodiment and comparative example are shown in Table 1.
[0153] Table 1
[0154]
[0155] Test method:
[0156] (1) Test of the total number of pores in the maximum cross-section of secondary particles in the positive electrode active material: Plasma cutting was used to cut along the maximum cross-section of the secondary particles, and the cut cross-section was photographed under a scanning electron microscope (SEM). A single secondary particle was taken for analysis, and the total number of pores N in the maximum cross-section of a single secondary particle was calculated. The particle size D of the secondary particles could be obtained directly by SEM measurement. N and D are the average values obtained from measuring 5 secondary particles.
[0157] (2) Test of particle size distribution parameters of secondary particles in positive electrode active material: The particle size was tested using a Malvern 3000 laser particle size analyzer according to the test method of GB / T24533-2019. After obtaining the Dn10, Dn50 and Dn90 data of secondary particles, Kn90 was calculated. Kn90=(Dn90-Dn10) / Dn50.
[0158] (3) First discharge specific capacity test of secondary battery: Charge to 4.3V with constant current at 0.1C, then charge to 4.3V with constant voltage, and then discharge to 3.0V with 0.1C to test the first discharge specific capacity of secondary battery.
[0159] (4) Cyclic performance test of secondary battery: The initial discharge capacity C1 was measured at 25℃, 3V~4.3V, 1C charge and discharge for one cycle; the discharge capacity C2 was obtained after 80 cycles, and the capacity retention rate after 80 cycles was calculated as C2 / C1.
[0160] The total number of pores in the maximum cross-section of the secondary particles and the particle size distribution parameters of the secondary particles were tested on the positive electrode active materials prepared by the above embodiments and comparative examples. The first discharge specific capacity and cycle performance of the secondary batteries prepared by the above embodiments and comparative examples were also tested. The test results are shown in Table 2.
[0161] Table 2
[0162]
[0163] According to the test data in Table 2, the positive electrode active materials prepared through Examples 1-5, by controlling the total number N of pores in the maximum cross-section of the secondary particles to be greater than 260, the particle size D of the secondary particles to be in the range of 2μm to 9μm, and controlling the particle size distribution parameter of the secondary particles to be in the range of 0.3 to 1.1, so that the shrinkage factor of the positive electrode active material is greater than or equal to 26 pores / μm, increases the specific surface area of the positive electrode active material while increasing the volume of pores in the positive electrode active material. Furthermore, the initial discharge specific capacity of the secondary batteries prepared through Examples 1-5 is increased to over 215mAh / g, which is more than 11.4% higher than that of Comparative Example 1 (193mAh / g) and Comparative Example 2 (184mAh / g). The capacity retention rate of the secondary batteries prepared through Examples 1-5 after 80 cycles is increased to over 94.5%, which is more than 14% higher than that of Comparative Example 1 (80.4%) and Comparative Example 2 (73.9%). Therefore, it can be seen that the positive electrode active materials prepared based on the examples of this application have achieved significant results. In the prepared secondary battery, a larger specific surface area of the positive electrode active material can increase the contact area between the positive electrode active material and the electrolyte, improve the contact quality of the interface between the positive electrode active material and the electrolyte, optimize the ion and electron transport channels in the secondary battery, reduce the ion and electron transport resistance, and improve the ion and electron transport efficiency, which is beneficial to increasing the battery capacity of the secondary battery. Furthermore, by increasing the volume of pores in the positive electrode active material, this embodiment can, on the one hand, provide filling space for the electrolyte in the positive electrode active material, further improving the contact quality of the interface between the positive electrode active material and the electrolyte. On the other hand, it can also increase the volume shrinkage of the positive electrode active material after delithiation during the charging process of the secondary battery, providing sufficient expansion space for the lithium intercalation expansion of the negative electrode active material, relieving the internal pressure of the secondary battery, reducing the degree of compression and damage caused to the positive and negative electrode active materials by the lithium intercalation expansion process of the negative electrode active material, which is beneficial to improving the cycle performance of the secondary battery and extending its service life.
[0164] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.
[0165] The above provides a detailed description of the positive electrode active material, preparation method, secondary battery, and electrical device provided in this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A positive electrode active material, characterized in that, The positive electrode active material comprises primary particles, which aggregate to form secondary particles, and satisfies the following conditions: c = N / (D × Kn90); Wherein, c_cells / μm represents the shrinkage factor of the positive electrode active material, which is used to reflect the volume shrinkage characteristics of the positive electrode active material during the delithiation process, and c ≥ 26_cells / μm; N represents the total number of pores in the maximum cross-section of the secondary particle; Dμm represents the particle size of the secondary particles; Kn90 represents the particle size distribution parameter of the secondary particles in the positive electrode active material, which reflects the uniformity of the particle size distribution of the secondary particles in the positive electrode active material.
2. The positive electrode active material according to claim 1, characterized in that, The particle size distribution parameters of the secondary particles satisfy: Kn90 = (Dn90 - Dn10) / Dn50; Wherein, Dn90μm represents the particle size corresponding to a cumulative distribution percentage of 90% for the secondary particles; Dn10μm represents the particle size corresponding to a cumulative distribution percentage of 10% for the secondary particles; and Dn50μm represents the particle size corresponding to a cumulative distribution percentage of 50% for the secondary particles.
3. The positive electrode active material according to claim 1 or 2, characterized in that, 0.3≤Kn90≤1.
1.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that, N ≥ 260.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that, 2μm≤D≤9μm.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that, The positive electrode active material includes materials with the molecular formula Li. a Ni b Co c Mn d M m N n Compounds of O2; Where b+c+d+m+n=1, and 1 <a<1.1,0≤b<1,0<c≤1,0≤d≤0.5,0<m≤0.1,0<n≤0.1; M and N are each independently selected from at least one of Ti, Al, Zr, Y, Sr, Nb, W, Sb, Ce, Mg, Co, Mo, V, and B.
7. The positive electrode active material according to any one of claims 1 to 6, characterized in that, The particle size Dn50 of the primary particles is 100nm to 300nm; the particle size Dn50 of the primary particles represents the particle size corresponding to the cumulative distribution percentage of the primary particles being equal to 50%.
8. The positive electrode active material according to any one of claims 1 to 7, characterized in that, The particle size Dn50 of the secondary particles is 3μm to 18μm; the particle size Dn50 of the secondary particles represents the particle size corresponding to the cumulative distribution percentage of the secondary particles being equal to 50%.
9. A method for preparing a positive electrode active material, characterized in that, The method includes: A hydroxide precursor material was prepared by mixing a transition metal salt solution, an alkaline solution, and a complexing agent solution. The first mixture obtained by mixing the hydroxide precursor material with an alkali metal source and a first additive is subjected to sintering treatment to obtain the raw material. Based on the raw materials, the positive electrode active material as described in any one of claims 1 to 8 is prepared.
10. A secondary battery, characterized in that, It includes a positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, the positive active material layer including the positive active material as described in any one of claims 1 to 8.
11. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 10, wherein the secondary battery serves as the power supply for the electrical equipment.
